Synthesis of metal-binding amino acids - Deck, Katherine E. V.; Brittain, William D. G. (Organic & Biomolecular Chemistry)
The ability for amino acid residues to bind metals underpins the functions of metalloproteins to conduct a plethora of critical processes in living organisms as well as unnatural applications in the fields of catalysis, sensing and medicinal chemistry. The capability to access metal-binding peptides heavily relies on the ability to generate appropriate building blocks. This review outlines recently developed strategies for the synthesis of metal binding non-proteinogenic amino acids. The chemistries to access, as well as to incorporate these amino acids into peptides is presented herein.